Assessing the effectiveness of using terminology bank in translating Chinese Medicine texts: a comparative study - Kua, Baohe (Nanyang Technological University, 2023)
Traditional Chinese Medicine (TCM) has its practices date all the way back to more than two thousand years ago, with its roots based off Chinese philosophy and culture. The globalisation of TCM has warranted the need to translate TCM knowledge into English as a global language to reach to wider audiences, and the handling of such texts can be used together with machine translation (MT), terminology bank and computer aided tools in the translation of TCM texts. This study aims to look into the effectiveness of the use of a terminology bank in translating Chinese Medicine texts with MT and its advantages and limitations. An evaluation on the MT processing of a text from a Chinese-English bilingual TCM textbook using Amazon Translate and a custom terminology bank built from the WHO International Standard Terminologies on Traditional Chinese Medicine published in 2022 was done by looking at frequency of identified terms in the output text and descriptive analysis on selected examples. It was found that the use of terminology bank in translating TCM texts can help with providing the correct and proper TCM terms, though human inventions are still required to ensure the readability of the target text for high quality translations.